Proc. 14th Int. Conf. On Global Research and Education, Inter-Academia 2015 2016
DOI: 10.7567/jjapcp.4.011112
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium state of bifilar helix as element of metamaterials

Abstract: In the present article, we study the long bifilar helix in which electric currents are quasi-stationary, i.e. the wavelength of the electromagnetic field is much longer than the turn of the helix. All components of the force acting on a physically small element of one helix from the other helix having a big length are calculated. The case when the currents in the two helices have the same direction relative to the x axis is considered. The dependence of the radial component of the force of interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…These radial components of the forces describe the mutual attraction or repulsion of two helices and exist both for a symmetrical double helix and in the case of mutual shift of two helices along their common axis. It has been shown that there exists a certain equilibrium helix pitch angle (α 0 ≈ 38 deg) at which the radial component of the magnetic force vanishes, which means the absence of radial attraction or repulsion of the elementary current in the second helix with respect to the entire first helix [44,45]. At this particular angle α 0 the force radial component of the helices' magnetic interaction changes sign.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These radial components of the forces describe the mutual attraction or repulsion of two helices and exist both for a symmetrical double helix and in the case of mutual shift of two helices along their common axis. It has been shown that there exists a certain equilibrium helix pitch angle (α 0 ≈ 38 deg) at which the radial component of the magnetic force vanishes, which means the absence of radial attraction or repulsion of the elementary current in the second helix with respect to the entire first helix [44,45]. At this particular angle α 0 the force radial component of the helices' magnetic interaction changes sign.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the result obtained in this article appear promising: the direction of the radial force of electric currents attraction or repulsion in two helical strands depends on the double helix pitch angle. The critical pitch angle of the double helix, at which the radial force of the magnetic interaction of two helices changes its direction, is α 0 ≈ 38 deg [44,45]. At the same time, the DNA helix in its natural condition is characterized by the pitch angle α exp = 28.4 deg [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations